THE INFLUENCE OF WORKLOAD ON THE ACADEMIC ACHIEVEMENT OF RAJA ALI HAJI MARITIME UNIVERSITY STUDENTS WHO WORK WHILE STUDYING - Angrainny, Laila Desmita; Putri, Natasya Delia (Universitas Negeri Makassar, 2025)
This study aims to analyze the influence of workload on the academic achievement of students who work while attending university. The dual responsibility of working and pursuing higher education is a growing phenomenon among university students, driven by financial demands and the pursuit of early career experience. Using a quantitative method with an associative approach, this research involved respondents selected based on specific criteria. Data were collected through questionnaires and analyzed using simple linear regression with SPSS. The findings reveal that workload has a significant influence on students' academic achievement. This result suggests that students who juggle work and academic commitments need effective time and energy management to succeed in their studies. Furthermore, the study also highlights the importance of support from both educational institutions and workplaces to help students maintain a healthy balance between their educational and professional responsibilities.